Informatics for One Health - Hollis, Kate Fultz; Mougin, Fleur; Soualmia, Lina F. (Yearbook of medical informatics, 2023)
Objectives: To introduce the 2023 International Medical Informatics Association (IMIA) Yearbook by the editors. Methods: The editorial provides an introduction and overview to the 2023 IMIA Yearbook where the special topic is “Informatics for One Health”. The special topic, survey papers and some best papers are discussed. The section changes in the Yearbook editorial committee are also described. Results: IMIA Yearbook 2023 provides many perspectives on a relatively new topic called “One Digital Health”. The subject is vast, and includes the use of digital technologies to promote the well-being of people and animals, but also of the environment in which they evolve. Many sections produced new work in the topic including One Health and all sections included the latest themes in many specialties in medical informatics. Conclusions: The theme of “Informatics for One Health” is relatively new but the editors of the IMIA Yearbook have presented excellent and thought-provoking work for biomedical informatics in 2023.